Sistem Presensi Berbasis Sidik Jari untuk Peningkatan Disiplin Kehadiran Aparat Desa - Rahmatulloh, Alam; Gunawan, Rohmat (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2019)
Since the issuance of Law No. 6 of 2014 concerning Villages, the process of organizing village government is demanded to be more optimal. The performance of village officials must continue to be improved, in order to provide better services to the community. The work activities of village officials are influenced by the level of attendance and discipline of work schedules and hours. The process of recording data on the presence of village officials needs to be managed properly, because it affects the performance of services to the community. Conventional attendance data recording, is done by affixing a signature to a book or attendance form that is done at work time. Weaknesses of this process, including not knowing exactly the hours of work and hours of return and attendance data is easily manipulated by entrusting signatures to others. Based on these problems, it is proposed to implement a fingerprint-based attendance recording system. The process of recording and preparing attendance reports is supported by software that has been designed to handle attendance data processing, and attendance data reports can be printed directly so that it can produce more accurate information and data. The results of the implementation of a fingerprint-based attendance system were able to improve the discipline of village officials by providing authentic data on complete attendance.